2023
DOI: 10.21053/ceo.2022.01319
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Non-coding RNAs in Cholesteatoma of the Middle Ear

Abstract: Cholesteatoma of the middle ear is a common disease in otolaryngology that is receiving increasing attention. It is estimated that over 5 million people around the world are suffering from middle ear cholesteatoma. The yearly frequency of middle ear cholesteatoma is detailed as 9.2 per 100,000 in adults and 3 per 100,000 in children. Without timely discovery and intervention, cholesteatomas can become perilously large and attack intratemporal structures, coming about in various intra- and extracranial complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Middle ear cholesteatoma is a relatively common disease in otolaryngology [ 20 ], the pathogenesis and mechanisms of which have been drawing growing attention. Numerous studies revealed the roles of miRNAs in the formation and progression of cholesteatoma [ 9 , 10 ].In the present study, we identified 121 significantly differentially expressed miRNAs in acquired retraction pocket cholesteatoma tissues via small RNA sequencing. Among them, 56 miRNAs were upregulated, and 65 miRNAs were downregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Middle ear cholesteatoma is a relatively common disease in otolaryngology [ 20 ], the pathogenesis and mechanisms of which have been drawing growing attention. Numerous studies revealed the roles of miRNAs in the formation and progression of cholesteatoma [ 9 , 10 ].In the present study, we identified 121 significantly differentially expressed miRNAs in acquired retraction pocket cholesteatoma tissues via small RNA sequencing. Among them, 56 miRNAs were upregulated, and 65 miRNAs were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Several research suggested the genetic associations of cholesteatoma in syndromic and familial forms [7,8]. Also, researchers have recently paid attention to the role of non-coding RNAs in cholesteatoma pathogenesis which have certain therapeutic potential [9,10]. Complete removal of the lesion, preservation of normal middle ear mucosa, and restoration of the middle ear ventilation and drainage system during surgery help reduce the recurrence of cholesteatoma [11][12][13].…”
Section: Introductionmentioning
confidence: 99%